Effect of carbonation on the pore solution of mortar. (April 2019) - De Weerdt, K.; Plusquellec, G.; Belda Revert, A.; Geiker, M.R.; Lothenbach, B.
Abstract: Understanding the changes in the pore solution upon carbonation is crucial with respect to comprehending the mechanisms of reinforcement corrosion in carbonated mortar or concrete. In this paper we used Cold Water Extraction (CWE), a rapid leaching method, on profile ground powder from partially carbonated Portland cement and Portland-fly ash cement mortars to study changes in the pore solution composition. Carbonation decreased the free alkali metal content measured with CWE, which matched with the portlandite profiles determined by thermogravimetry and the carbonation depth detected with pH indicator. The alkali metal uptake by carbonation products was confirmed by SEM-EDS and thermodynamic modelling. Besides the decrease in the alkali metal concentration in the pore solution upon carbonation, we observed for both binders a considerable increase in chlorine and sulphur concentrations. This can further accelerate corrosion in carbonated concrete.